MicroRNA-10a-3p Improves Cartilage Degeneration by Regulating CH25H-CYP7B1-RORα Mediated Cholesterol Metabolism in Knee Osteoarthritis Rats - Li, Xiaochen; Zhang, Li; Shi, Xiaoqing; Liao, Taiyang; Zhang, Nongshan; Gao, Yifan; Xing, Runlin; Wang, Peimin (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a worldwide degenerative joint disease that seriously impaired the quality of life of patients. OA has been established as a disease with metabolic disorder. Cholesterol 25-hydroxylase (CH25H) was proved to play a key role in cartilage cholesterol metabolism. However, the biological function and mechanism of CH25H in OA remains further investigation. Growing researches have proved the vital roles of miRNAs in OA progression. In this study, we screened out miR-10a-3p through high-throughput miRNA sequencing which may bind to CH25H. Molecular mechanism investigation indicated that miR-10a-3p is an upstream target of CH25H. Functional exploration revealed miR-10a-3p suppressed the inflammatory responses, cholesterol metabolism and extracellular matrix (ECM) degradation in primary chondrocytes. Moreover, rescue assays implied that miR-10a-3p reversed CH25H plasmids induced inflammatory cytokine production and ECM degradation. Furthermore, the OA rat model was established to explore the function of miR-10a-3p in vivo. The results showed that miR-10a-3p can recover the OA features through targeting CH25H/CYP7B1/RORα axis. In conclusion, these findings implied a crucial role of miR-10a-3p/CH25H/CYP7B1/ RORα axis in OA, which may provide a promising therapeutic strategy for OA.